Analisis Hubungan Sekolah Dengan Masyarakat Dalam Proses Pembelajaran di SD Negeri 16 Landau Siling - Agnes Veronika; Ason; Joni Albar (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2026)
Abstract: This study aims to analyze the relationship between the school and the community in the learning process at SD Negeri 16 Landau Siling, Sayan District, Melawi Regency. The research employed a descriptive qualitative approach with participants consisting of the principal, teachers, students’ parents, and community leaders selected purposively. Data were collected through questionnaires, in-depth interviews, observation, and documentation, and were analyzed interactively through data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources, techniques, and time. The results show that the relationship between the school and parents as well as the community is socially good, but it has not yet been structured and sustained institutionally. Communication remains reactive and focuses mainly on academic aspects, while learning support at home has not developed into comprehensive pedagogical assistance. School–community collaboration is still incidental and has not been supported by formal partnership programs. This study emphasizes the importance of strengthening planned and sustainable partnerships to improve the quality of learning.Keywords: School and Community Relations, Learning Process. Abstrak: Penelitian ini bertujuan untuk menganalisis hubungan sekolah dengan masyarakat dalam proses pembelajaran di SD Negeri 16 Landau Siling, Kecamatan Sayan, Kabupaten Melawi. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek kepala sekolah, guru, orang tua siswa, dan tokoh masyarakat yang dipilih secara purposive. Data dikumpulkan melalui angket, wawancara mendalam, observasi, dan dokumentasi, serta dianalisis secara interaktif melalui reduksi data, penyajian data, dan penarikan kesimpulan. Keabsahan data dijaga melalui triangulasi sumber, teknik, dan waktu. Hasil penelitian menunjukkan bahwa hubungan sekolah dengan orang tua dan masyarakat tergolong baik secara sosial, tetapi belum terstruktur dan berkelanjutan secara kelembagaan. Komunikasi masih bersifat reaktif dan berfokus pada aspek akademik, sementara dukungan pembelajaran di rumah belum berkembang menjadi pendampingan pedagogis yang komprehensif. Kolaborasi sekolah–masyarakat masih insidental dan belum didukung program kemitraan resmi. Penelitian ini menegaskan pentingnya penguatan kemitraan yang terencana dan berkelanjutan untuk meningkatkan kualitas pembelajaran.Kata Kunci: Hubungan Sekolah dan Masyarakat, Proses Pembelajaran.